Analysis of Digital Marketing Public Relations Strategy in Efforts to Market BBK (Quality Fuel) Products through the My Pertamina Application - Kurniawan, Achmad; Zinaida, Rahma Santhi; Jabir, Bastian; Helmi, Sulaiman (Communica : Journal of Communication, 2024)
This study aims to analyze the Public Relations (PR) strategy of Pertamina Patra Niaga Regional Region of South Sumatra in marketing Special Fuel ((QUALITY FUEL)) products through the My Pertamina application, as well as evaluate its impact on customer loyalty and fuel usage during a certain period. This study uses a qualitative approach with data collection methods through in-depth interviews, direct observation, and documentation. Primary data was obtained from interviews with Pertamina's Public Relations, while secondary data came from related literature and media reports. The analysis was carried out to understand the effectiveness of marketing strategies and the application of digital technology in increasing the use of Quality fuel. The results of the study show that the PR strategy through the My Pertamina application significantly increases customer loyalty. The app facilitates transactions and provides a points-based loyalty program that is effective in attracting customers. The increase in the use of Quality fuel products, especially Pertamax and Dex Series, was recorded during the homecoming period with an increase in demand of up to 64%. The Public Relations strategy through the My Pertamina application is effective in increasing customer loyalty and promoting (QUALITY FUEL) products. However, there are challenges in the implementation of digital technology, especially among people who are not used to using applications. Further education is needed to optimize the benefits of this app across customer segments